Meat Tenderness: Underlying Mechanisms, Instrumental Measurement, and Sensory Assessment - Frank Dunshea; Minh Ha; Peter Purslow; Rhonda K. Miller; Robyn Warner; Rozita Spiroska Vaskoska; Tommy L. Wheeler; Xin Li (Meat and Muscle Biology, 2021)
Meat tenderness is a quality trait critical to consumer acceptance and determines satisfaction, repeat purchase, and willingness to pay premium prices. The aim of this review was to explore instrumental and sensory methods for assessing meat tenderness in relation to underlying mechanisms and to identify limitations of existing methods, as well as opportunities for global standardization. To achieve this, tenderness is defined, and the main instrumental methods for tenderness are presented, including their historical development and standardization. The significant determinants of meat tenderness are presented, encompassing connective tissue and cross-links, myofibrillar integrity, sarcomere length, intramuscular fat, and protein denaturation during cooking. The development of sensory methods for assessing meat is presented as well as the link between objective measures of texture and consumer tenderness scores. Recent advances in statistical methods for sensory data are discussed, and considerations for future research are outlined.